EPLAODV: Energy Priority and Link Aware Ad-hoc On-demand Distance Vector Routing Protocol for Post-disaster Communication Networks - Soomro, M. A.; Channa, M. I.; Hussain, Z.; Ahmed, M. (Engineering, Technology & Applied Science Research, 2020)
In Mobile Ad-hoc Networks (MANETs) the major issue between nodes for data transfer is link quality. The majority of the MANET routing protocols try to maintain the link quality between nodes but still need improvement. This paper focuses on link quality between nodes in an ad hoc network in emergency scenarios through the design of the Energy Priority and Link Aware Ad-hoc On Demand Distance Vector (EPLAODV) routing protocol. EPLAODV improves the link quality between nodes through SNR. For performance analysis, the NS2.35 network simulator was used. Simulation time and traffic load were the major simulation parameters. From the simulation results, it is observed that EPLAODV performs better than AODV.